Cytopathologic features of NUT midline carcinoma: A series of 26 specimens from 13 patients. Issue 12 (11th July 2016) - Bishop, Justin A.; French, Christopher A.; Ali, Syed Z.
Abstract : BACKGROUND: NUT midline carcinoma (NMC) is an increasingly recognized neoplasm defined by rearrangements of the nuclear protein in testis ( NUT ) gene (also known as NUTM1 ). NMC is important to diagnose for prognostic and diagnostic reasons, but to date, only a small case series and rare case reports of the cytopathologic features of NMC have been published. METHODS: All NMC specimens (confirmed by molecular testing and/or NUT immunoreactivity) with cytopathologic material available were identified at 2 academic centers. All smears were reviewed, and the cytologic characteristics were described. RESULTS: Twenty‐six cytopathologic specimens of NMC were identified from 13 patients: 8 men and 5 women ranging in age from 16 to 68 years (mean, 35 years). The NMCs arose in the mediastinum (n = 4), sinonasal tract (n = 4), neck (n = 2), lung (n = 1), lung and mediastinum (n = 1), and kidney (n = 1). Cytologic specimens included serous cavity effusions (n = 13), fine‐needle aspirates (n = 9), bronchial brushings (n = 2), bronchial lavage (n = 1), and bronchial washings (n = 1). Ancillary studies were performed on cell blocks for only 6 samples from 4 patients: immunohistochemistry (n = 6) and flow cytometry (n = 1). All 13 NMCs had corresponding surgical pathology material. The NUT rearrangement status was known in 10 cases, and in 3 cases, the diagnosis was established by immunoreactivity for NUT. On cytologic smears, the NMCs were mostly hypercellular with monotonous, small to midsize, primitive‐appearing cells largely distributed singly in a discohesive pattern. The tumor cells had round to oval nuclei that appeared mostly naked and devoid of cytoplasm. The nuclei varied in chromatin density from mostly pale, open chromatin to a hyperchromatic, neuroendocrine‐type appearance, often with focal cell‐to‐cell molding, and most examples had a distinct, small nucleolus. CONCLUSIONS: NMC is a recently recognized tumor that should be considered in the differential diagnosis of small round cell tumors, especially but not exclusively in the mediastinum and the head and neck. The cytologic features of NMC overlap considerably with those of other neoplasms, and a definitive diagnosis depends on a demonstration of NUT translocation by either immunohistochemical or molecular means. Cancer Cytopathol 2016;124:901–908 . © 2016 American Cancer Society . Abstract : NUT midline carcinoma is a recently described malignant neoplasm defined by rearrangements involving NUT and most often arising in the mediastinum or head and neck. The cytopathologic features of NUT midline carcinoma overlap considerably with those of other high‐grade, small round cell malignancies.